2004
DOI: 10.1074/jbc.m313093200
|View full text |Cite
|
Sign up to set email alerts
|

Vif Overcomes the Innate Antiviral Activity of APOBEC3G by Promoting Its Degradation in the Ubiquitin-Proteasome Pathway

Abstract: Viruses must overcome diverse intracellular defense mechanisms to establish infection. The Vif (virion infectivity factor) protein of human immunodeficiency virus 1 (HIV-1) acts by overcoming the antiviral activity of APOBEC3G (CEM15), a cytidine deaminase that induces G to A hypermutation in newly synthesized viral DNA. In the absence of Vif, APOBEC3G incorporation into virions renders HIV-1 non-infectious. We report here that Vif counteracts the antiviral activity of APOBEC3G by targeting it for destruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
383
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(402 citation statements)
references
References 41 publications
11
383
1
7
Order By: Relevance
“…Perhaps the simplest way to prevent A3G action would, therefore, be to block virion encapsidation-and this is what Vif does. Though there have been reports of Vif directly impeding packaging (Mariani et al 2003;Opi et al 2007), Vif's principal function is to induce the polyubiquitylation and subsequent proteasomal degradation of A3G, thereby depleting the pool of cytosolic A3G available for incorporation into assembling virus particles (Conticello et al 2003;Marin et al 2003;Sheehy et al 2003;Stopak et al 2003;Yu et al 2003;Mehle et al 2004b;Kobayashi et al 2005). Vif accomplishes this by simultaneously binding to both A3G and the cullin5-elongin B/C-Rbx ubiquitin ligase, thus serving as an adaptor to recruit the ligase complex to its substrate ( Yu et al 2003; figure 2).…”
Section: Vif Inhibits Apobec3g Function By Inducing Proteasomal Degramentioning
confidence: 99%
“…Perhaps the simplest way to prevent A3G action would, therefore, be to block virion encapsidation-and this is what Vif does. Though there have been reports of Vif directly impeding packaging (Mariani et al 2003;Opi et al 2007), Vif's principal function is to induce the polyubiquitylation and subsequent proteasomal degradation of A3G, thereby depleting the pool of cytosolic A3G available for incorporation into assembling virus particles (Conticello et al 2003;Marin et al 2003;Sheehy et al 2003;Stopak et al 2003;Yu et al 2003;Mehle et al 2004b;Kobayashi et al 2005). Vif accomplishes this by simultaneously binding to both A3G and the cullin5-elongin B/C-Rbx ubiquitin ligase, thus serving as an adaptor to recruit the ligase complex to its substrate ( Yu et al 2003; figure 2).…”
Section: Vif Inhibits Apobec3g Function By Inducing Proteasomal Degramentioning
confidence: 99%
“…A3G was also demonstrated in testes, ovaries, and a number of tumor cell lines (14). There is limited information concerning the factors that control expression of A3G, but its level of mRNA does not change with HIV-1 infection (11,16). A3G inhibits both the R5 and X4 strains of HIV-1 (5).…”
Section: Stimulation Of Cell Surface Ccr5 and Cd40 Molecules By Theirmentioning
confidence: 99%
“…It is now well established that HIV-1 Vif can counteract the human cytidine deaminase APOBEC3G (APO3G). The inhibition of APO3G's antiviral effects has been attributed to a reduction in cellular expression of APO3G protein, which is due to Vif-mediated degradation of APO3G by cytoplasmic proteasomes (6,20,25,27,34,37,43). On the other hand, we recently found that Vif could prevent encapsidation of a degradation-resistant APO3G variant, suggesting that Vif can inhibit the APO3G antiviral activity through multiple independent mechanisms (29).…”
mentioning
confidence: 99%